Eksistensi Pendekatan Studi Islam Ditengah Ilmu-Ilmu Keislaman Lainnya - Apris, Apris; Kamal, Tamrin; Hakim, Rosmiati (Journal Education And Islamic Studies, 2024)
Islamic Studies as a growing discipline has an important role in facing contemporary challenges, both in normative and empirical aspects. This article aims to analyse the development and contribution of Islamic Studies in responding to global issues, such as modernity, pluralism, and morality crisis, using a qualitative approach. Searches were conducted on online research platforms, namely Website Dimension and VOSViewer, to map trends and dominant topics in Islamic Studies. Through bibliometric data analysis, this article explores the interaction between historical, sociological, philosophical, and hermeneutical studies in Islamic Studies and its contribution to the integration of science and religion. The results of this study show that Islamic Studies has the capacity to adapt to the dynamics of the times and remain relevant in bridging between Islamic scientific traditions and the challenges of modern life. The findings are expected to provide new insights for further development in the study of Islamic Studies and its role in the transformation of world civilisation.